Applications of Artificial Intelligence in Pediatric Dentistry: A Narrative Review - Chiranjit Ghosh; Bhaswati Chakraborty; Amitava Bora; Pradip Kumar Mandal (Journal of Primary Care Dentistry and Oral Health, 2026)
Abstract Artificial intelligence (AI) is significantly transforming pediatric dentistry, offering advancements in diagnostic accuracy, treatment planning, and patient care. This narrative review explores the various applications of AI, including the detection of dental caries and supernumerary teeth, behavior management, and treatment planning for traumatic dental injuries. AI-driven tools, such as machine learning models and deep learning algorithms, enhance precision and efficiency in clinical practice. However, challenges such as data privacy concerns and high implementation costs must be addressed to fully harness AI’s potential. This review aligns with the journal’s scope by synthesizing current evidence on AI applications in a specialized area of pediatric healthcare, offering insights for clinicians, researchers, and policymakers. This review highlights the promise of AI in revolutionizing pediatric dental care and underscores the need for further research to overcome existing barriers.